The Emerging Role of Macrophages in Chronic Cholangiopathies Featuring Biliary Fibrosis: An Attractive Therapeutic Target for Orphan Diseases - Cadamuro, Massimiliano; Girardi, Noemi; Gores, Gregory J.; Strazzabosco, Mario; Fabris, Luca (Frontiers in Medicine, 2020)
Cholangiopathies are a heterogeneous group of chronic liver diseases caused by different types of injury targeting the biliary epithelium, such as genetic defects and immune-mediated attacks. Notably, most cholangiopathies are orphan, thereby representing one of the major gaps in knowledge of the modern hepatology. A typical hallmark of disease progression in cholangiopathies is portal scarring, and thus development of effective therapeutic approaches would aim to hinder cellular and molecular mechanisms underpinning biliary fibrogenesis. Recent lines of evidence indicate that macrophages, rather than more conventional cell effectors of liver fibrosis such as hepatic stellate cells and portal fibroblasts, are actively involved in the earliest stages of biliary fibrogenesis by exchanging a multitude of cues with cholangiocytes, which promote their recruitment from the circulating compartment owing to a senescent or an immature epithelial phenotype. Two cholangiopathies, namely primary sclerosing cholangitis and congenital hepatic fibrosis, are paradigmatic of this mechanism. This review summarizes current understandings of the cytokine and extracellular vesicles-mediated communications between cholangiocytes and macrophages typically occurring in the two cholangiopathies to unveil potential novel targets for the treatment of biliary fibrosis.